KESEJAHTERAAN KELUARGA MENURUT PERSPEKTIF ISLAM: KAJIAN KUALITATIF: Family Wellbeing According to Islamic Perspective: A Qualitative Study - Mohd Saat, Ahmad Hariri; Azahari, Raihanah (Jurnal Syariah, 2022)
This study focused on the factors leading to a happily married life. Three married couples who have been awarded mithali and mawaddah family were chosen as samples using purposive sampling method. In depth-structured interviews were conducted to investigate their experience of being happily married and what factors they think are important to be happily married until they are awarded mithali family (until they were given mithali family award). The interview data were then analyzed strictly according to the themes that have been determined along with the evidence from the interviews conducted. Thirteen categories that emerged after coding the data were religiosity, compromise and commitment, marital satisfaction, wise conflict resolution, good communication, presence of children in the marriage, economic status, positivity in the relationship, respect, trust, understanding, lovingness and no mistreatment involved in the relationship. This study has important implications for married couples, counsellors and those directly involved in drafting the Family Wellbeing Index at the Ministry of Women, Family and Community Development.